Sustainable Water Management and One Health - Taiwo Bakare Abidola; Abisola Eniola Folorunso; Mariam Omonike Akib; Olamide Jelil Olaoye; Adams Oladapo Adewale; Sandra Etoniru; Abdulhakeem Abdulsalam Oladipupo (Darul Yasin Al Sys, 2025)
This study investigates the linkages between sustainable water management and public health outcomes within the One Health framework in selected rural communities. Using a mixed methods approach, data were obtained through household surveys, key informant interviews, and laboratory testing of water sources. Quantitative results revealed extensive microbial contamination, with Escherichia coli present in 68% of surface water samples and 29% testing positive for Cryptosporidium oocysts. More than 60% of surveyed households reported incidences of diarrhea, and statistical analysis showed a significant correlation between the use of untreated water and disease prevalence. Qualitative findings from stakeholders pointed to systemic challenges, including institutional fragmentation, inadequate sanitation infrastructure, and limited public awareness of zoonotic disease transmission. Notably, familiarity with the One Health approach was low among both local residents and health professionals. The integrated analysis highlights the need for coordinated, cross-sectoral interventions that incorporate infrastructure development, community education, and policy integration. These efforts are essential to mitigate the risks of waterborne diseases and enhance public health resilience in vulnerable settings. The study underscores the importance of the One Health model in addressing complex environmental health threats and advocates for its broader implementation to foster sustainable and equitable health outcomes.